Optimización Multiobjetivo en la Gestión de Cadenas de Suministro de Biocombustibles. Una Revisión de la Literatura - Aranda Pinilla, Johan Alexander; Orjuela Castro, Javier Arturo (Ingeniería, 2015)
Biofuel production has had constant growth in recent years and is expected it keeps growing in the medium and long term, mainly driven by the environmental benefits they could bring compared to fossil fuel, such as the reduction of greenhouse gas emissions, positive energy balance and economic development for producer countries. However, despite its benefits, there are concerns about the environmental and social impacts that its production and distribution may generate. The multi-objective or multi-criteria decision theory has been used in recent years as a framework for integrating the various objectives in decision-making on biofuel supply chains. This article aims to present a review of the main concepts and multi-objective optimization methods as well as their application in the design and planning of biofuel supply chains. The study shows that cost is the most frequent economic objective, greenhouse emissions are the most frequently used environmental objective and the number of created jobs is the most considered social criterion, leaving out important aspects such as food safety.